Legal Regulation of Kazakhstan’s Transition to the Green Economy - YERKINBAYEVA, Lazzat; TELEUYEV, Galym; KALYMBEK, Bakytzhan; NURMUKHANKYZY, Daniya; KUDERINA, Assiya (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).18, 2021)
To preserve nature, it is necessary to carefully monitor the state of the natural environment, normalize and prevent industrial emissions, and develop and implement waste-free and resource-saving technologies. Chemical safety is an important element of the national security of the Republic of Kazakhstan in “green economy” conditions. The main goals of safe management are prevention, reduction, minimization of toxic substances’ potentially harmful effects on public health and environment. Today, humanity has begun to realize that any economic branch first of all affects the environment. Therefore, the world community is considering various mechanisms for preserving the environment, and certainly, the idea of a green economy is one of them. A green economy is not just an opportunity, but a mandatory path of development for all countries which strive to ensure a secure future for their citizens. The present research aims to suggest recommendations concerning the legal issues of the transition to a green economy and to improve the regulatory framework of the Republic of Kazakhstan. In the course of the study, the authors propose theoretical and practical recommendations for improving the current state mechanism for the transition to a green economy.